Amnioinfusion Compared With No Intervention in Women With Second-Trimester Rupture of Membranes: A Randomized Controlled Trial. Issue 1 (January 2019) - van Kempen, Liselotte E. M.; van Teeffelen, Augustinus S.; de Ruigh, Annemijn A.; Oepkes, Dick; Haak, Monique C.; van Leeuwen, Elisabeth; Woiski, Mallory; Porath, Martina M.; Bax, Caroline J.; van Wassenaer-Leemhuis, Aleid G.; Mulder, Antonius L.; van der Ham, David P.; et al.
Abstract : OBJECTIVE: To assess the effectiveness of amnioinfusion in women with second-trimester preterm prelabor rupture of membranes. METHODS: We performed a nationwide, multicenter, open-label, randomized controlled trial, the PPROM: Expectant Management versus Induction of Labor-III (PPROMEXIL-III) trial, in women with singleton pregnancies and preterm prelabor rupture of membranes at 16 0/7 to 24 0/7 weeks of gestation with oligohydramnios (single deepest pocket less than 20 mm). Participants were allocated to transabdominal amnioinfusion or no intervention in a one-to-one ratio by a web-based system. If the single deepest pocket was less than 20 mm on follow-up visits, amnioinfusion was repeated weekly until 28 0/7 weeks of gestation. The primary outcome was perinatal mortality. We needed 56 women to show a reduction in perinatal mortality from 70% to 35% (β error 0.20, two-sided α error 0.05). RESULTS: Between June 15, 2012, and January 13, 2016, we randomized 28 women to amnioinfusion and 28 to no intervention. One woman was enrolled before the trial registration date (June 19, 2012). Perinatal mortality rates were 18 of 28 (64%) in the amnioinfusion group vs 21 of 28 (75%) in the no intervention group (relative risk 0.86, 95% CI 0.60–1.22, P= .39). CONCLUSION: In women with second-trimester preterm prelabor rupture of membranes and oligohydramnios, we found no reduction in perinatal mortality after amnioinfusion. CLINICAL TRIAL REGISTRATION: NTR Dutch Trial Register, NTR3492. Abstract : Amnioinfusion does not improve perinatal outcome in pregnancies complicated by second-trimester preterm prelabor rupture of membranes.